Clinical characteristics and molecular etiology of partial 17α-hydroxylase deficiency diagnosed in 46,XX patients - Zhang, Duoduo; Yao, Fengxia; Luo, Min; Wang, Yanfang; Tian, Tiffany; Deng, Shan; Tian, Qinjie (Frontiers in Endocrinology, 2022)
Complete 17α-hydroxylase deficiency (17OHD) is relatively common, with typical juvenile female genitalia, severe hypertension, hypokalemia, and absence of sexual development, but partial (or non-classical) 17OHD (p17OHD) is extremely rare. The p17OHD patients can present with a broad spectrum of symptoms in 46 XX karyotype depending on their specific gene mutations, including various degree of spontaneous breast development after puberty, recurrent ovarian cysts, oligomenorrhea and infertility. This is a retrospective analysis of p17OHD cases from 1997 to 2021 in a Chinese tertiary hospital. Ten patients were recruited from unrelated families according to clinical data. The genotypes of these 10 patients were further determined by sequencing the CYP17A1 and POR genes. Their clinical characteristics were summarized based on manifestations, hormone profiles, and responses to treatments. All eight post-pubertal patients had abnormal menses. All patients had enlarged multilocular ovaries, and eight had a history of bilateral ovarian cystectomy prior to a definite diagnosis of p17OHD. Their sex hormone levels were in accordance to hypogonadism with mildly elevated follicle-stimulating hormone levels, and oral contraceptives effectively suppressed the ovarian cysts. Of the six patients who underwent plasma renin activity tests, four showed results below the reference range. Fourteen alleles with a CYP17A1 mutation were found. Exon 6 is one of the most frequent mutation sites (5/14), and four out of these five are c.985_987delTACinsAA, which was the most common mutation. Two patients fit the clinical diagnostic criteria for p17OHD, but turned out to have POR rather than CYP17A1 mutations. In Case 2, c.1220dupA was a newly reported mutation of CYP17A1. Therefore, 46 XX p17OHD patients are borne with very fragile ovarian function and diverse mutations of CYP17A1 and need genetic differentiation with PORD,, and their multi-ovarian cysts can be managed conservatively for fertility preservation. This study specifically focus on p17OHD in 46 XX, which implies its complex genetic causes with novel genetic findings and summarizes patients’ puzzling spectrum of clinical manifestations.